CGA G-13 large-scale silane release test – Part II. Unconfined silane–air explosions. (July 2015) - Ngai, Eugene Y.; Fuhrhop, Ron; Chen, Jenq-Renn; Chao, Jenny; Bauwens, C. Regis; Mjelde, Crystal; Miller, Gary; Sameth, Jerry; Borzio, John; Telgenhoff, Michael; Wilson, Bruce
Abstract: A series of large-scale field trials to better understand the explosion characteristics of silane–air was conducted by the G-13 Silane Task Group under the direction of the Compressed Gas Association (CGA) and its guidelines. Silane was released from a high-pressure source into the open atmosphere, and overpressure measurements of unconfined silane–air explosions were taken at different locations away from the explosion centre. It was found that significant blast effects can result from relatively small releases of silane (around 0.1 kg). It is possible to achieve these small releases during an accidental discharge from a "pigtail" connection (a small-diameter coiled tube that connects a silane tube trailer to a process). Therefore, accidental silane explosions should be recognized as significant and possible events when handling silane. These results were also used in the proposed revision of ANSI/CGA G-13 Storage and Handling of Silane and Silane Mixtures. Highlights: Large-scale field trials were conducted in order to evaluate the hazards of accidental silane–air explosions. An unconfined explosive mixture was generated by releasing silane into the open atmosphere from a high-pressure source. Overpressure measurements were taken at varying distances from the explosion centre. Significant blast effects were found to result from a relatively small release of 0.1 kg. These results were used to revise ANSI/CGA G-13 storage and handling of silane and silane mixtures.